The Effect of Microbial Preparations on the Mineral Nutrition of Seedlings and the Productivity of a Fruit Nursery in the Steppe Crimea - Klimenko, O. E.; Plugatar, Y. V.; Klimenko, N. I. (Russian journal of plant physiology, 2023)
The influence of microbial preparations (MP) on mineral nutrition, the productivity of the fruit plant nursery, as well as soil fertility indicators in the steppe Crimea were studied. The research was carried out in field small-plot experiments. The variants of experiment were: Azotobacterin (AB) and Diazophyte (DA)—diazotrophs; Phosphoenterin (PE) is a phosphate mobilizer; Complex of microbial preparations (CMP). It was established that MPs increase the total nitrogen content in the leaves of apricot seedlings: AB—by 73%; mahaleb cherry: DA—by 25%. The content of total phosphorus in the leaves of apricot and almond seedlings increased by 9–29% under the influence of PE and CMP relative to the control. The potassium content in the leaves of cherry plum and mahaleb cherry seedlings increased under the influence of CMP by 7 and 44% respectively. The use of PE and CMP led to an improvement in plant nutrition with nitrogen—on apricot and peach seedlings by 28–64%, phosphorus—by 9–70%, potassium—on cherry plum and apricot by 6–33% when growing seedlings in the second field of the nursery. The use of MP had little effect on the content of mobile forms of basic nutrients and humus in the soil. Improving the mineral nutrition of fruit plant seedlings using MP contributed to an increase in the output of standard planting material per unit area. The most effective were PE on peach and cherry seedlings, CMP—on apricot and cherry plum, which made it possible to obtain additional 3–29 thousand seedlings per hectare.